Rapid Isolation of Human Endothelial Cells from Whole Blood Using S-Endo1 Monoclonal Antibody Coupled to Immuno-Magnetic Beads: Demonstration of Endothelial Injury after Angioplasty - George, F; Brisson, C; Poncelet, P; Laurent, J C; Massot, O; Arnoux, D; Ambrosi, P; Klein-Soyer, C; Cazenave, J P; Sampol, J (Thrombosis and Haemostasis, 1992)
The presence in whole blood of circulating endothelial cells (EC) has been a subject of debate for many years. It could represent a good marker of vessel injury. We demonstrate here that human endothelial cells can be directly isolated and identified in circulating blood by means of an endothelial cell specific monoclonal antibody, S-Endol, coupled to micromagnetic beads. The specificity and efficacy of the assay were established using normal blood samples with cultured EC added. Specific rosettes formed between EC and beads could subsequently be isolated with a magnet. The rosetted cells were recovered with a yield >80%. Their endothelial origin was confirmed by the positive labelling of von Willebrand factor and thrombomodulin, as well as the presence of Weibel-Palade bodies. We applied this method to demonstrate significantly increased levels of EC in venous and arterial human blood samples in patients undergoing heart catheterization. This new whole blood immuno-separation method may be useful in determining endothelial cell injury in vascular disorders.